Evaluating interfacial shear stresses in composite hollo - Aiham Adawi; Maged A. Youssef; Mohamed E. Meshaly (Alexandria Engineering Journal, 2016)
Analytical evaluation of the interfacial shear stresses for composite hollowcore slabs with concrete topping is rare in the literature. Adawi et al. (2014) estimated the interfacial shear stiffness coefficient (ks) that governs the behavior of the interface between hollowcore slabs and the concrete topping using push-off tests. This parameter is utilized in this paper to provide closed form solutions for the differential equations governing the behavior of simply supported composite hollowcore slabs. An analytical solution based on the deformation compatibility of the composite section and elastic beam theory, is developed to evaluate the shear stresses along the interface. Linear finite element modeling of the full-scale tests presented in Adawi et al. (2015) is also conducted to validate the developed analytical solution. The proposed analytical solution was found to be adequate in estimating the magnitude of horizontal shear stress in the studied composite hollowcore slabs.